Preclinical and Clinical Evidence for the Involvement of Sphingosine 1-Phosphate Signaling in the Pathophysiology of Vascular Cognitive Impairment - Chua, Xin Ying (HUMANA PRESS INC, 2021)
10.1007/s12017-020-08632-0